Chlorotoxin as a Drug Delivery System to treat Glioblastoma - Fawzy, Ahmed Faadil (2021)
This thesis describes the generation of a number of new conjugates and their evaluation against brain tumour derived cell lines. Chlorotoxin (ClTx) is a 36-amino acid protein found in the venom of the deathstalker scorpion (Leiurus quinquestriatus). ClTx binds to brain tumours and can stop invasion and metastasis of glioma cells, such as glioblastoma multiforme (GBM). Perillyl alcohol (POH) is a monoterpene derived from the mevalonate pathway. It is an effective chemotherapeutic agent against several cancers such as breast, liver and pancreatic by causing the cells to undergo apoptosis. Temozolomide (TMZ) is a DNA methylating agent which adds a methyl group at the N7 or O6 position of guanine in the DNA causing GBM cells to undergo apoptosis. TMZ is currently used as the main chemotherapeutic drug for GBM. The aim of this research was to first purify recombinant ClTx-constructs, followed by synthesis of cytotoxic ligands that will be conjugated to ClTx and finally, test these CITx-ligand conjugates for cytotoxicity against GBM cells. In this research, ClTx constructs were successfully cloned and purified. The ClTx inhibited U87 cell migration while ClTx conjugated to fluorescein showed binding of this protein on the surface and inside U87 cells within 40 min after exposure. POH was modified to create linkers enabling conjugation of the ligand to ClTx. POH was finally conjugated to ClTx through a cleavable ester link. The ClTx-POH conjugate showed no cytotoxic activity upto a concentration of 10 μM. Instead a variant of TMZ, known as N3P-TMZ, which has a propargyl group instead of a methyl group at the N3 position of temozolomide, was synthesised in order to assess its cytotoxicity against GBM cells. The N3P-TMZ requires modification to allow conjugation to ClTx which can then create a cytotoxic drug which should specifically target GBM.